THE USE OF DIGITAL STORYTELLING TO IMPROVE STUDENTSâ SPEAKING SKILL - Sari, Farnia; Anggraini, Risa (JURNAL DIDASCEIN BAHASA, 2017)
ABSTRACT: The use of digital storytelling is a media to increase the studentsâ speaking that involved maximally throughout the studentsÂ  ability to create their own digital storytelling, so they can explore their imagination and active in involving speaking activities. Thus, it is interested in finding out whether there was significant improvement of studentsâ speaking skill by using digital storytelling and whether there was a significant difference in speaking achievement between the tenth grade students who were taught by using digital storytelling and those who were not. This method used wasÂ  quasi experimentalÂ  design. The population of the study is the tenth grade students of SMAN 18 Palembang. The purposive sampling technique was used to select the sample consisting of 72 students on this study.Â  TheÂ  data were collected by speaking test in the form of monologue. The collected data was analyzed by using paired sample t-test and independent sample t-test.Â  The results of paired sample t-test showed that the studentsâ speaking skill were improved andÂ  The result of independent sample t-test showed that the value of t-obtainis higher (2.142) than the value of t-table (1.994). Â The table also showed that the p-output of studentsâ speaking skill in both groups was lower than the level of significant 0.05. The significant (2-tailed) 0.036 < 0.05 and t-obtain 2.142 > t-table 1.994.Â  It can be concluded that there was a significant difference between the students who were taught by using digital storytelling and those who were not.Â Â Key words: Digital storytelling, speaking skill.